The Failure of Empathy and the Power of Art: An Ethical Relationship with the Impossible Other —Take Kimsooja's "A Needle Woman" as an example (Journal of Global Arts Studies, 2025)
Background： Empathy, as an interdisciplinary concept of multidimensional discussion, is both a key psychological phenomenon and the ultimate realization of ethical pursuit. The dilemma of empathy in real situations provides the point of departure for artistic expression, for art does not evade the distance between self and other in the failure of empathy, but rather transforms this distance into the starting point of aesthetic experience. Objective： This study situates the “impossible possibility” of forgiveness and empathy within the essence of ethical relations, exploring the possibility of empathy in ethical contexts. Through the sensuous experience of art, it demonstrates how artistic works can transcend the barriers of incommunicability, establish connections with the Other, and ultimately realize the ethical power of empathy in aesthetic experience. Methods： This study employed the case study method, using Kimsooja's "A Needle Woman" as the case study, to explore the unempathetic empathy that is evoked by artistic works. Results： Empathy is not a homogeneous projection of the experiences of others, but rather, within the aesthetic realm of art, through the acceptance and reflection of what cannot be empathized with, it awakens the subject's awareness of the limitations of their self-perception. Conclusion： The value of empathy lies not in eliminating the ethical dilemmas of the unreachable others. Through the active recognition of the incommensurable in artistic works, the subject transcends the limitations of self-awareness and ultimately constructs a more ethically significant empathic relationship with others.
Keywords: Empathy; Forgiveness; the Other; "A Needle Woman"